2012
DOI: 10.1371/journal.pone.0045957
|View full text |Cite
|
Sign up to set email alerts
|

The VP3 Factor from Viruses of Birnaviridae Family Suppresses RNA Silencing by Binding Both Long and Small RNA Duplexes

Abstract: RNA silencing is directly involved in antiviral defense in a wide variety of eukaryotic organisms, including plants, fungi, invertebrates, and presumably vertebrate animals. The study of RNA silencing-mediated antiviral defences in vertebrates is hampered by the overlap with other antiviral mechanisms; thus, heterologous systems are often used to study the interplay between RNA silencing and vertebrate-infecting viruses. In this report we show that the VP3 protein of the avian birnavirus Infectious bursal dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 104 publications
(149 reference statements)
1
33
0
Order By: Relevance
“…Moreover, the recognition of naked IBDV dsRNA by the RNA cytoplasmic sensor MDA5 in DF-1 cells was found to activate chIFN-␤ expression (59), but it was also described that VP3 interferes with this recognition (40). This is consistent with the notion that the binding of VP3 to IBDV dsRNA shields the virus genome from host RNA sensors, thus preventing PKR-mediated apoptosis (34,71). Regarding this, it is interesting to note that a stoichiometric analysis of IBDV structural components showed that infectious IBDV particles harbor four dsRNA genome segments associated (in the form of RNPs) with ca.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, the recognition of naked IBDV dsRNA by the RNA cytoplasmic sensor MDA5 in DF-1 cells was found to activate chIFN-␤ expression (59), but it was also described that VP3 interferes with this recognition (40). This is consistent with the notion that the binding of VP3 to IBDV dsRNA shields the virus genome from host RNA sensors, thus preventing PKR-mediated apoptosis (34,71). Regarding this, it is interesting to note that a stoichiometric analysis of IBDV structural components showed that infectious IBDV particles harbor four dsRNA genome segments associated (in the form of RNPs) with ca.…”
Section: Discussionsupporting
confidence: 69%
“…Even a dsRNA-binding protein from E. coli , a species that is not targeted by an RNAi response, is able to suppress RNAi under overexpression conditions (53). It has been shown previously that the IBDV, IPNV and DXV VP3 proteins have the capacity to suppress RNAi (54). However, these studies were done in a heterologous system and the in vivo relevance in a relevant host remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…VP3 was previously reported to bind IBDV genomic dsRNA to protect the viral genome from the host RNA silencing machinery and inhibit PKR-mediated apoptosis (18,21). To investigate whether viral proteins suppressed IFN-␤ expression by binding to naked IBDV genomic dsRNA, we identified the viral proteins binding to dsRNA and examined IFN-␤ expression under these conditions.…”
Section: Ibdv Infection Did Not Induce Efficient Expression Of Type Imentioning
confidence: 99%
“…5D, ectopically expressed VP3 protein from IPNV and DXV also bound dsRNA. The basic amino acid motif 99 K 102 R 105 K 106 K in the ␣1 helix of VP3 has been shown to be responsible for binding small duplex RNA (18,21), so we speculated that this region may be involved in the inhibition of chIFN-␤ expression. Figure 5E indicates that the VP3 patch 1 mutant, in which the basic amino acids 99 K, 102 R, 105 K, and 106 K are replaced by acidic amino acid D, had almost no dsRNA binding activity, and a further 97 R-to-D substitution had no additional effect on dsRNA binding activity.…”
Section: Ibdv Infection Did Not Induce Efficient Expression Of Type Imentioning
confidence: 99%